Indoor localization using ultra-wideband - Ong, Cayvann Juay Soong (Nanyang Technological University, 2024)
The attention on indoor positioning is increasing because accurately sensing indoor positions is difficult due to signal deflection by objects. This document outlines the study, creation, and assessment of indoor positioning technologies utilizing Ultra-wideband (UWB). UWB can determine its location by communicating with stationary UWB anchors placed throughout the surroundings. Nevertheless, it does not work well in non-line-of-sight (NLOS) conditions. A comprehensive survey is necessary for many indoor positioning systems to ensure there are no obstacles obstructing the anchor devices' path, as pinpoint accuracy in locating objects is crucial.